2006
DOI: 10.1124/dmd.106.009399
|View full text |Cite
|
Sign up to set email alerts
|

N-GLUCURONIDATION OF PERFLUOROOCTANESULFONAMIDE BY HUMAN, RAT, DOG, AND MONKEY LIVER MICROSOMES AND BY EXPRESSED RAT AND HUMAN UDP-GLUCURONOSYLTRANSFERASES

Abstract: ABSTRACT:N-Alkylperfluorooctanesulfonamides have been used in a range of industrial and commercial applications. Perfluorooctanesulfonamide (FOSA) is a major metabolite of N-alkylperfluorooctanesulfonamides and has a long half-life in animals and in the environment and is biotransformed to FOSA N-glucuronide. The objective of this study was to identify and characterize the human and experimental animal liver UDP-glucuronosyltransferases (UGTs) that catalyze the N-glucuronidation of FOSA. The results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 27 publications
4
22
0
Order By: Relevance
“…The responsible mechanism must therefore have been metabolism, either to PFOS or a phase II conjugate. Xu et al found that PFOSA is metabolized to an N-glucuronide in isolated hepatic cells, 11,42 but no glucuronide conjugates of PFOSA were detected in this study, consistent with glucuronidation of PFOSA being only a minor metabolic pathway in vivo in rats. 39 Although PFOSA and other PFOS-precursors have been detected in human blood and in wildlife tissues, 1 few studies have investigated the isomer profile of PFOS-precursors in environmental samples.…”
Section: ■ Results and Discussionsupporting
confidence: 93%
“…The responsible mechanism must therefore have been metabolism, either to PFOS or a phase II conjugate. Xu et al found that PFOSA is metabolized to an N-glucuronide in isolated hepatic cells, 11,42 but no glucuronide conjugates of PFOSA were detected in this study, consistent with glucuronidation of PFOSA being only a minor metabolic pathway in vivo in rats. 39 Although PFOSA and other PFOS-precursors have been detected in human blood and in wildlife tissues, 1 few studies have investigated the isomer profile of PFOS-precursors in environmental samples.…”
Section: ■ Results and Discussionsupporting
confidence: 93%
“…This contrasts with several other enzymes, such as UGT1A3 and UGT2B7, that can catalyze the N-glucuronidation of certain aglycones in addition to other glucuronidation reactions (Green and Tephly, 1998;Zenser et al, 2002;Zhang et al, 2004;Borlak et al, 2006;Xu et al, 2006). This difference in function could be reflected by the primary structure of these enzymes, and an inspection of the amino acid sequences of all the human UGTs has indeed revealed an interesting observation.…”
Section: Discussionmentioning
confidence: 80%
“…Our newly developed analytical method was applied to the determination of nicotine and cotinine glucuronidation rates by UGT1A4 and UGT1A9, enzymes reported previously to catalyze nicotine glucuronidation (Kuehl and Murphy, 2003), and by UGT2B7, an enzyme that is involved in the glucuronidation of many structurally diverse xenobiotics including N-glucuronidation reactions (Zhang et al, 2004;Xu et al, 2006). It is noteworthy that the activity of UGT2B10 was also determined because our preliminary studies with this enzyme showed efficient N-glucuronidation of certain other compounds (Kaivosaari S, Koskinen M, and Finel M, manuscript in preparation).…”
Section: Resultsmentioning
confidence: 99%
“…The difference in the method of microsome preparation may influence glucuronidation activities. However, in past studies, species differences of glucuronidation activities have been assessed with microsomes prepared by different methods (Xu et al, 2006;Cai et al, 2010).…”
Section: Discussionmentioning
confidence: 99%